Let the integral in question be given by \begin{align} f_{n}(x) = \int_{1}^{x} \binom{t-1}{n} \, dt. \end{align} The integral can also be seen in the form \begin{align} f_{n}(x) = \frac{1}{n!} \, \int_{1}^{x} \frac{\Gamma(t) \, dt}{\Gamma(t-n)} = \frac{(-1)^{n+1}}{n!} \int_{1}^{1-x} (u)_{n} \, du. \end{align} The first few values are \begin{align} f_{0}(x) &= x-1 \\ f_{1}(x) &= \frac{(x-1)^{2}}{2!} \\ f_{2}(x) &= \frac{2}{4!} \, (2 x^{3} - 9 x^{2} + 12 x - 5). \end{align}

The question then becomes:

  1. What is the general series form of $f_{n}(x)$ ?
  2. Is there a connection to known special functions? In particular can $f_{n}(x)$ be related to the Bernoulli numbers of the second kind?
  • 1
    $\begingroup$ @MarkusScheuer Indeed a factor of 2 was missing. Thanks for the review and correction. $\endgroup$ – Leucippus Jun 27 '15 at 18:36

There is indeed a relation with the Bernoulli numbers of second kind. If I'm right, this is the result :

Theorem : generating function of $f_n(x)$ $$\sum_{n=0}^{+\infty} f_n(x)z^n = \dfrac{(1+z)^{x-1}-1}{\log (1+z)}$$

Corrolary : $$f_n(x) = \sum_{k=0}^n {{x-1}\choose{k+1}} \dfrac{b_{n-k}}{(n-k)!}$$

I'll present here mainly the "formal" steps to get to this result, I'll skip the details of convergence, derivation under integral and all. Start with : $$f_n(x)=\dfrac{1}{n!} \int_1^x \frac{\Gamma(t)}{\Gamma(t-n)} \text{d}t=\dfrac{1}{n!} \int_1^x (t-1)(t-2) \cdots (t-n) \text{d}t$$

Now introduce $g(t,y)=y^{t-1}$. We have $\dfrac{\partial^n g}{\partial y^n}(t,y)=(t-1)(t-2) \cdots (t-n)y^{t-n-1}$. Thus : $$\begin{array}{rcl} f_n(x,y) & = & \displaystyle \frac{1}{n!} \int_1^x (t-1)(t-2) \cdots (t-n)y^{t-n-1} \text{d}t\\ & = & \displaystyle \frac{1}{n!} \dfrac{\partial^n \;}{\partial y^n} \left( \int_1^x y^{t-1} \text{d}t\right) \\ & = & \displaystyle \frac{1}{n!} \dfrac{\partial^n \;}{\partial y^n} \left( \frac{y^{x-1}-1}{\log(y)}\right) \\ & = & \end{array}$$

We have $f_n(x)=f_n(x,1)$. Thus, we get (modulo some good argument for the Taylor expansion) : $$\boxed{\sum_{n=0}^{+\infty} f_n(x)z^n = \sum_{n=0}^{+\infty} \displaystyle \left. \frac{1}{n!} \dfrac{\partial^n \;}{\partial y^n} \left( \frac{y^{x-1}-1}{\log(y)}\right) \right|_{y=1} z^n = \dfrac{(1+z)^{x-1}-1}{\log (1+z)}}$$

This demonstrates the theorem. The corollary is a direct consequences of the following series exapnsion : $$\displaystyle \dfrac{(1+z)^{x-1}-1}{z} = \sum_{n=0}^{+\infty} {{x-1}\choose{n+1}}z^n \; \; \; \; \; \; \; \text{and} \; \; \; \; \; \; \; \displaystyle \frac{z}{\log(1+z)} = \sum_{n=0}^{+\infty} \frac{b_n}{n!}z^n$$

$f_n(x)$ is then given by the Cauchy product : $$\boxed{f_n(x) = \sum_{k=0}^n {{x-1}\choose{k+1}} \dfrac{b_{n-k}}{(n-k)!}}$$

I'm not sure we can go any further than this.

By curiosity, how did you come across this problem ?


Here's another variation of the theme based upon Stirling Numbers.

Starting from \begin{align*} f_n(x)&=\int_1^x\binom{t-1}{n}dt =\frac{1}{n!}\int_1^x{(t-1)}_ndt =\frac{1}{n!}\int_0^{x-1}{(u)}_ndu \end{align*} we can use the Stirling Numbers of the first kind $s(n,k)$ which can be defined for $n\geq 0$ and $0\leq k \leq n$ by \begin{align*} {(u)}_n=\sum_{k=0}^ns(n,k)u^k\tag{1} \end{align*}

Using this relationship we obtain for $n\geq 0$

\begin{align*} f_n(x)&=\frac{1}{n!}\int_0^{x-1}\sum_{k=0}^ns(n,k)u^kdu\\ &=\frac{1}{n!}\sum_{k=0}^ns(n,k)\int_0^{x-1}u^kdu\\ &=\frac{1}{n!}\sum_{k=0}^ns(n,k)\left.\frac{1}{k+1}u^{k+1}\right|_0^{x-1}\\ &=\frac{1}{n!}\sum_{k=0}^ns(n,k)\frac{1}{k+1}(x-1)^{k+1} \end{align*}

We conclude

\begin{align*} f_n(x)= \frac{1}{n!}\sum_{k=0}^n\frac{s(n,k)}{k+1}(x-1)^{k+1}&\qquad n\geq 0\tag{2}\\ \end{align*}

An exponential generating function $\sum_{n=0}^{\infty}f_n(x)\frac{z^n}{n!}$ can be derived from the generating function of the Stirling Numbers of the first kind.

Generating function: In accordance to the answer of @SylvainL. we claim

The following is valid

\begin{align*} \sum_{n=0}^{\infty}f_n(x)\frac{z^n}{n!}=\frac{(1+z)^{x-1}-1}{\log(1+z)} \end{align*}

We obtain from (1) \begin{align*} (1+z)^u&=\sum_{n=0}^{\infty}\binom{u}{n}z^n\\ &=\sum_{n=0}^{\infty}{(u)}_n\frac{z^n}{n!}\\ &=\sum_{n=0}^{\infty}\left(\sum_{k=0}^ns(n,k)u^k\right)\frac{z^n}{n!}\tag{3} \end{align*}

In the following we consider $f_n(x+1)$ instead of $f_n(x)$.

We observe

\begin{align*}\sum_{n=0}^{\infty}f_n(x+1)\frac{z^n}{n!} &=\sum_{n=0}^{\infty}\left(\sum_{k=0}^{n}\frac{s(n,k)}{k+1}x^{k+1}\right)\frac{z^n}{n!}\tag{4}\\ &=\int_0^x\sum_{n=0}^{\infty}\left(\sum_{k=0}^{n}s(n,k)u^{k}\right)\frac{z^n}{n!}du\\ &=\int_0^{x}(1+z)^udu\tag{5}\\ &=\int_0^xe^{u\log(1+z)}du\\ &=\left.\frac{1}{\log(1+z)}e^{u\log(1+z)}\right|_0^x\\ &=\frac{(1+z)^x-1}{\log(1+z)}\\ &\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\Box \end{align*} and the claim follows.


  • In (4) we use the representation (2) of $f_n(x)$

  • In (5) we use the generating function of $s(n,k)$ from (3)

Calculation for small values $n=0,1,2$:

Since $$s(0,0)=1,s(1,1)=1,s(2,1)=-1,s(2,2)=1$$ we obtain \begin{align*} f_0(x)&=s(0,0)(x-1)=x-1\\ f_1(x)&=s(1,1)\frac{1}{2}(x-1)^2=\frac{1}{2}(x-1)^2\\ f_2(x)&=\frac{1}{2}\left(s(2,1)\frac{1}{2}(x-1)^2+s(2,2)\frac{1}{3}(x-1)^3\right)\\ &=-\frac{1}{4}(x-1)^2+\frac{1}{6}(x-1)^3\\ &=\frac{1}{12}(2x^3-9x^2+12x-5) \end{align*}

Note: We don't need analytical considerations for the calculations above, since we can state that all calculations are done within the ring of formal power series.

  • $\begingroup$ This is a great view to the proposed problem. As always your work is great to learn from. $\endgroup$ – Leucippus Jun 27 '15 at 18:38
  • $\begingroup$ @Leucippus: You're welcome! Thanks for your nice comment! :-) $\endgroup$ – Markus Scheuer Jun 27 '15 at 18:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.